Ultrasound-Assisted Deep Eutectic Solvents Extraction of Polysaccharides From Morchella importuna: Optimization, Physicochemical Properties, and Bioactivities - Pan, Xu; Xu, Lijing; Meng, Junlong; Chang, Mingchang; Cheng, Yanfen; Geng, Xueran; Guo, Dongdong; Liu, Rongzhu (Frontiers in Nutrition, 2022)
In the present study, a high-efficiency and non-pollution extraction procedure, ultrasound-assisted technique with deep eutectic solvents (DESs), was applied for extraction of polysaccharides from Morchella importuna (MIP-D). The results exhibited that the system of DES was: mole ratio between choline chloride and oxalic acid of 2:1, water content of 90% (v/v), the optimal extraction parameters were as follows: extraction time of 31.2 min, extraction temperature of 62.1℃ and the liquid-solid ratio of 32.5:1 (v/w). Under these extraction parameters, the extraction yield of MIP-D was 4.5 times higher than hot water extraction method (HE), and had higher carbohydrate (85.27%) and sulfate contents (34.16%). Moreover, High Performance Liquid Chromatography (HPLC) and FT-IR spectrum analysis indicated that MIP-D was comprised of glucosamine, galactose, glucose, and mannose with molar ratios of 0.39:1.88:3.82:3.91, which contained the pyranose ring skeleton. High Performance Gel Permeation Chromatography (HPGPC) analysis revealed that MIP-D showed three fractions with molecular weights of 2.6×106, 7.3×104 and 3.7×103 Da, which were lower than those of polysaccharides extracted by HE. In vitro tests proved that MIP-D possessed excellent antioxidant and inhibited α-amylase and α-glucosidase inhibitory activity. Therefore, DESs (choline chloride-oxalic acid) as a high-efficiency and non-pollution solvent alternative can be applied to the separation of bioactive polysaccharides from M. importuna.